2021
DOI: 10.3389/fcell.2021.640169
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profile of Myelin in the Zebrafish Brain

Abstract: The velocity of nerve conduction along vertebrate axons depends on their ensheathment with myelin. Myelin membranes comprise specialized proteins well characterized in mice. Much less is known about the protein composition of myelin in non-mammalian species. Here, we assess the proteome of myelin biochemically purified from the brains of adult zebrafish (Danio rerio), considering its increasing popularity as model organism for myelin biology. Combining gel-based and gel-free proteomic approaches, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 107 publications
2
24
0
Order By: Relevance
“…Myelination by Oligodendrocytes. Similar to other vertebrates, zebrafish oligodendrocytes make multiple myelin sheaths on many axons upon differentiation (Figure 3), and although some differences in components have been noted the overall molecular composition and ultrastructural nature of myelin in zebrafish and mammals appears broadly similar (Jahn et al, 2009(Jahn et al, , 2020Czopka and Lyons, 2011;Preston and Macklin, 2015;Czopka, 2016;Siems et al, 2021) (Figure 3). By live imaging of oligodendrocytes in zebrafish over time using transgenic reporters, Czopka et al (2013) found that individual cells initiate formation of essentially all of their sheaths within a matter of hours following the initiation of the first sheath, pointing to a restricted period in which oligodendrocytes have to select axons for myelination.…”
Section: Oligodendrocytementioning
confidence: 89%
“…Myelination by Oligodendrocytes. Similar to other vertebrates, zebrafish oligodendrocytes make multiple myelin sheaths on many axons upon differentiation (Figure 3), and although some differences in components have been noted the overall molecular composition and ultrastructural nature of myelin in zebrafish and mammals appears broadly similar (Jahn et al, 2009(Jahn et al, , 2020Czopka and Lyons, 2011;Preston and Macklin, 2015;Czopka, 2016;Siems et al, 2021) (Figure 3). By live imaging of oligodendrocytes in zebrafish over time using transgenic reporters, Czopka et al (2013) found that individual cells initiate formation of essentially all of their sheaths within a matter of hours following the initiation of the first sheath, pointing to a restricted period in which oligodendrocytes have to select axons for myelination.…”
Section: Oligodendrocytementioning
confidence: 89%
“…For this reason, the genetic mechanisms that orchestrate myelinating glial cell development requires continued exploration. Over the past few decades, we and others have noted expression of cd59 that is conserved in developing myelinating glial cells across multiple organisms, including zebrafish, rodents, and humans (Gerber et al, 2021;Howard et al, 2021;Marisca et al, 2020;Marques et al, 2018Marques et al, , 2016Piller et al, 2021;Saunders et al, 2019;Siems et al, 2021;Sun et al, 2013;Wolbert et al, 2020;Zajicek, 1995;Zhu et al, 2019). Despite these observations, there had been little exploration into the function of Cd59 in the developing nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Artwork created by Ashtyn T. Wiltbank with Illustrator (Adobe) based on previous schematics and electron micrographs published in (Ackerman and Monk, 2016;Cunningham and Monk, 2018;Jessen and Mirsky, 2005). features in several RNA sequencing (RNAseq) and proteomic analyses of zebrafish and rodent myelinating glial cells (Gerber et al, 2021;Howard et al, 2021;Marisca et al, 2020;Marques et al, 2018Marques et al, , 2016Piller et al, 2021;Saunders et al, 2019;Siems et al, 2021;Wolbert et al, 2020;Zhu et al, 2019), all of which demonstrate high expression of cd59 in developing oligodendrocyte lineage cells (OLCs) and SCs. cd59 continues to be expressed in juvenile and adult zebrafish (Saunders et al, 2019;Siems et al, 2021;Sun et al, 2013) and becomes the 4 th most abundant CNS myelin protein in adult zebrafish (Siems et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already early gel-based comparisons between CNS myelin fractions purified from various fish and tetrapod species revealed that the clades comprise overlapping but divergent sets of major myelin proteins 8, 12 . More recently, this finding was extended to low-abundant constituents when quantitative mass spectrometry allowed comparing the CNS myelin proteome between zebrafish and mice 13 . By quantitative proteome analysis, MBP is highly abundant in CNS myelin of either species.…”
Section: Introductionmentioning
confidence: 92%